Synthesising carbo-nitrides of some d-group transition metals using a solar furnace at PSA - Shohoji, Nobumitsu (2014)
Carbo-nitride synthesis was undertaken using a solar furnace at PSA in flowing N2/Ar gas mixture under total pressure 1 atm and processing temperature T = 1600ºC for some d-group transition elements (Ti; Zr, V, Nb, Mo, W) starting from 1.5G/M (graphite/metal powder mixture with mole ratio 1.5:1) compact to ensure co-presence of free carbon with the reaction product. Clear X-ray diffraction (XRD) evidence of formation of carbo-nitride was detected for Ti (IVa group metal) showing higher N content in the carbo-nitride synthesised in N2 gas environment at partial pressure p(N2) = 1 atm than that at p(N2) = 0.5 atm. For M = V and Nb (Va group metals), formation of mono-carbide MC single-phase was detected in the N2 environment showing no evidence of formation of carbo-nitride in spite of presence of N2 in the environment. For M = Mo and W (VIa group metals), formation of higher carbide, among several options of carbide phases, appeared to be promoted in the N2 gas environment although, like in cases with the Va group metals, no evidence of dissolution of N into the reaction product was detected. As such, at T = 1600ºC in N2 gas environment up to p(N2) = 1 atm under concentrated solar beam, carbo-nitride formed from the 1.5G/M mixture only for IVa group metal (Ti) but not for Va and VIa group metals. Anyway, it seemed certain that N2 gas affected somehow the reaction path between G and M to yield the carbide phase for M = V, Nb, Mo and W.